Thermoelectric properties of bottom-up assembled Bi 2 S 3– x Te x nanocomposites. (1st January 2014) - Cadavid, Doris; Ibáñez, Maria; Anselmi-Tamburini, Umberto; Durá, Oscar Juan; Torre, Marco Antonio López de la; Cabot, Andreu
Bi 2 S 3– x Te x bulk nanocomposites with crystal domain sizes in the range from 50 nm to 100 nm were obtained from the reaction of Bi 2 S 3 nanorods with Te powder. The thermoelectric properties of the obtained nanocomposites were analysed in the temperature range from 0ºC to 300ºC. We observed how the thermoelectric properties of the material improved with the annealing temperature, being a spark plasma sintering process needed to maintain the material nanostructuration while maximising its electrical properties. Finally thermoelectric dimensionless figures of merit ZT up to 0.42 were obtained before any charge carrier concentration optimisation.